Code of Ethics of a Police Officer in the Context of Shaping the Security Environment of the Slovak Republic - Dominika, Dinušová (Magyar Rendészet, 2025)
In recent years, society has been marked by the occurrence of several risk factors (the pandemic, the war conflict in Ukraine, the increase in hate speech and the subsequent social polarisation that has reached a violent outcome). These aspects lead to a rethinking of the use of tools to eliminate tensions in different areas. One of them is the area of police ethics. The paper is devoted to selected content and structural elements used in the code of ethics of a police officer, which were aimed at strengthening the relationship between civil society and the police with the intention of positively shaping the security environment in the Slovak Republic. The paper is based on a theoretical analysis of three planes of the updated code of ethics: 1. the functions of the incorporated elements; 2. the means of implementation in the application practice; 3. research as a prerequisite for updating and a means of verification of the processing of the code of ethics. The third level is demonstrated on the field of credibility of the Police Force using the theoretical basis of the dialectical method. In 2022, the Slovak Regulation No. 41/2022 on the Code of Police Ethics of the Ministry of the Interior was adopted. The elements of virtue ethics were the main elements strengthening the implementation of the document. The document is divided into several parts, which are complementary to each other and fulfil mutual functions (explicative and motivational). The area of police ethics is significantly represented in the public perception of police work and ultimately has an impact on the overall shaping of the security environment in terms of forming the social consciousness of citizens and members of the Police Force.